Free Form Growth of Carbon Nanotube Microarchitectures on Stainless Steel Controlled via Laser‐Stimulated Catalyst Formation. Issue 16 (25th July 2017) - Reinhardt, Hendrik; Hellmann, Christoph; Nürnberger, Philipp; Kachel, Stefan; Hampp, Norbert
Abstract : Freeform growth of multiwalled carbon nanotubes (MWCNTs) is demonstrated on stainless steel AISI 304 (EN AW 1.4301) modified by pulsed laser irradiation. A nanosecond pulsed laser is utilized as a fast and facile tool for the generation of transition metal oxide precursors that promote spatially selective CNT growth upon chemical vapor deposition at 800 °C in an atmosphere comprising n ‐hexane and forming gas (5% H2 /95% N2 ). Investigations on a set of 12 precursor oxides indicate that iron‐rich transition metal oxides with high granularity provide best conditions for CNT growth. The laser‐induced generation of specific oxide precursors facilitates the fabrication of complex CNT microarchitectures. High levels of control over CNT location and height as well as the option to influence CNT alignment provide great flexibilities in design. The introduced technique displays a high degree of automatability and the potential for upscaling thus meeting the increasing demand for large scale fabrication of CNT‐enhanced devices. Abstract : Site‐selective carbon nanotube (CNT) growth on stainless steel is achieved by laser‐stimulated self‐organization of highly granular transition metal oxide precursors that transform into CNT catalysts upon thermal reduction thus enabling the fabrication of free‐form CNT microarchitectures with standard chemical vapor deposition equipment. The process facilitates control over CNT location and height as well as the alignment of CNT bundles.